Regent Regulation South Tapanuli Number 39 0f 2017 - Dinda Suciana Rambe (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The problem of this research lies in the practice of implementing South Tapanuli Regent Regulation Number 39 of 2017 concerning Violence Against Children in West Angkola District, South Tapanuli. And what is the view of Islam regarding cases of violence against children. The formulation of the research problem is how the practice of implementing the South Tapanuli regent's regulation number 39 of 2017 in handling violence against children, and what is the Islamic view on violence against children in West Angkola sub-district, South Tapanuli Regency. The basic theory used in this study is the understanding of the regent's regulations, the notion of child abuse and the contents of the regulations of the regent of South Tapanuli number 39 of 2017. The type of research used is a qualitative research study which intends to understand the phenomena experienced by research subjects such as behavior, perception , motivation, action and others. Sources of data obtained from people, places and paper. data collection techniques using field studies (observation, interviews, and documentation) and study to the library using a systematic discussion. The results of the research expressed in the thesis entitled Implementation of the South Tapanuli Regent Regulation Number 39 of 2017 concerning violence against children are the implementation of the South Tapanuli Regent's Regulation by conducting legal socialization and legal assistance and the application of healing for child victims of violence are applied in accordance with the needs of victims both in the field of law and healing the mental health of children who are victims of violence. But level of legal awareness and legal knowledge of the people of West Angkola District, South Tapanuli Regency is minimal which makes social problems of violence against children occur every year